1990
DOI: 10.1002/ajh.2830330210
|View full text |Cite
|
Sign up to set email alerts
|

The choice between splenectomy and medical treatment in patients with advanced agnogenic myeloid metaplasia

Abstract: The objective of the study was to explore the risks and benefits of splenectomy in advanced agnogenic myeloid metaplasia (AMM). We searched the literature (Medline, 1970-1987) for studies of postoperative survival, operative mortality and effects of splenectomy on painful splenomegaly, and portal hypertension or transfusion requirements in patients with AMM. We employed formal decision analysis to determine the relative value of medical and surgical treatment of advanced AMM. Results of data synthesis showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 17 publications
2
12
0
Order By: Relevance
“…As in 2 patients of the present series, it has been re ported previously that in some IM patients the in crease in hepatic myeloid metaplasia following sple nectomy can be so massive as to provoke prominent clinical and biological signs of liver dysfunction, even leading to death [10,14,15,18,19]. The reason why some patients develop this overwhelming complica tion is not known, and no preoperative clinical or lab oratory data have been found that predict this course [ …”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…As in 2 patients of the present series, it has been re ported previously that in some IM patients the in crease in hepatic myeloid metaplasia following sple nectomy can be so massive as to provoke prominent clinical and biological signs of liver dysfunction, even leading to death [10,14,15,18,19]. The reason why some patients develop this overwhelming complica tion is not known, and no preoperative clinical or lab oratory data have been found that predict this course [ …”
Section: Discussionmentioning
confidence: 67%
“…Some authors also include portal hypertension secondary to splenomegaly among the indications for splenectomy in IM [5,7,12], It must be pointed out, however, that the influ ence of splenectomy on both the disease evolution and the patients' survival is not clear. Thus, although some authors have reported a survival advantage for splenectomized IM patients [5], in a recent review, Ben-bassat et al [19] considered that splenectomy would prolong the survival of patients with thrombo cytopenia exclusively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Splenectomy can be proposed for symptomatic splenomegaly, but its high post-operative mortality and morbidity rates have undermined this procedure (Silverstein & ReMine, 1979;Malmaeus et al, 1986;Benbassat et al, 1990;Barosi et al, 1993). Currently, since none of these treatments has demonstrated any impact on the overall survival of these patients, they can only be considered as palliative.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for such an increase is not clear, but it has been speculated that a possible effect of splenectomy is to accelerate a pre-existing myeloid proliferation, since the procedure is not associated with a higher risk of acute leukaemia in healthy individuals. There are several reasons to consider splenectomy in IM, including symptomatic splenomegaly refractory to treatment, severe constitutional symptoms, uncontrollable haemolysis, transfusion-dependent anaemia unresponsive to therapy, portal hypertension secondary to increased portal flow, and marked thrombocytopenia (Benbassat et al, 1990;Barosi et al, 1993b;Lafaye et al, 1994;Tefferi et al, 2000). The benefits derived from splenectomy vary depending on the indication.…”
Section: Splenectomymentioning
confidence: 99%